2017
DOI: 10.1021/acs.langmuir.7b00957
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Local Heating on Marangoni Flows and Evaporation Kinetics of Pure Water Drops

Abstract: The effect of localized heating on the evaporation of pure sessile water drops was probed experimentally by a combination of infrared thermography and optical imaging. In particular, we studied the effect of three different heating powers and two different locations, directly below the center and edge of the drop. In all cases, four distinct stages were identified according to the emerging thermal patterns. In particular, depending on heating location, recirculating vortices emerge that either remain pinned or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 50 publications
4
24
0
Order By: Relevance
“… 49 Importantly, the simulated azimuthal relocation of the flow vortices within the droplets has also been confirmed and experimentally studied by Askounis et al. 50 …”
Section: Resultssupporting
confidence: 55%
“… 49 Importantly, the simulated azimuthal relocation of the flow vortices within the droplets has also been confirmed and experimentally studied by Askounis et al. 50 …”
Section: Resultssupporting
confidence: 55%
“…This led to the appearance of Marangoni flows. Various thermal patterns associated with hydrothermal waves have been observed [27]. The simulation results showed that the evaporation is jointly affected by the local heating of the droplet and the wettability of the substrate [28].…”
Section: Introductionmentioning
confidence: 98%
“…The thermocapillary rupture of the film in a cell with a built-in heater was experimentally investigated in [24,25,26]. The kinetics of evaporation under local heating of the droplet was studied in [27]. Point heating of the substrate with a laser was carried out in the area of the center or periphery of the drop.…”
Section: Introductionmentioning
confidence: 99%
“…Convective transport mechanisms stem from the buoyant and thermocapillary forces [7]. Since the dominance of thermocapillary forces over buoyant forces is well established [8,9], convection mechanisms associated with thermocapillarity have been the subject of the studies [10,11]. Thermocapillary effect refers to the pulling of the liquid from a warmer region to a colder region on the interface.…”
Section: Introductionmentioning
confidence: 99%